Treatment of particle/gas partitioning using level III fugacity models in a six-compartment system. (May 2021) - Li, Yi-Fan; Qin, Meng; Yang, Pu-Fei; Liu, Li-Yan; Zhou, Lin-Jun; Liu, Ji-Ning; Shi, Li-Li; Qiao, Li-Na; Hu, Peng-Tuan; Tian, Chong-Guo; Nikolaev, Anatoly; Macdonald, Robie
Abstract: In this paper, two level III fugacity models are developed and applied using an environmental system containing six compartments, including air, aerosols, soil, water, suspended particulate matters (SPMs), and sediments, as a "unit world". The first model, assumes equilibrium between air and aerosols and between water and SPMs. These assumptions lead to a four-fugacity model. The second model removes these two assumptions leading to a six-fugacity model. The two models, compared using four PBDE congeners, BDE-28, -99, −153, and −209, with a steady flux of gaseous congeners entering the air, lead to the following conclusions. 1. When the octanol-air partition coefficient ( K OA ) is less than 10 11.4, the two models produce similar results; when K OA > 10 11.4, and especially when K OA > 10 12.5, the model results diverge significantly. 2. Chemicals are in an imposed equilibrium in the four-fugacity model, but in a steady state and not necessary an equilibrium in the six-fugacity model, between air and aerosols. 3. The results from the six-fugacity model indicate an internally consistent system with chemicals in steady state in all six compartments, whereas the four-fugacity model presents an internally inconsistent system where chemicals are in equilibrium but not a steady state between air and aerosols. 4. Chemicals are mass balanced in air and aerosols predicted by the six-fugacity model but not by the four-fugacity model. If the mass balance in air and aerosols is achieved in the four-fugacity model, the condition of equilibrium between air and aerosols will be no longer valid. Graphical abstract: Image 1 Highlights: Rationality of equilibrium between air and aerosols in Level-III model is examined. A level-III model without equilibrium assumption is developed. Steady state and not equilibrium between air and aerosols is confirmed by the model. Equilibrium between air and aerosols leads a false steady state solution in a system. Steady state between air and aerosols should be used in Level-III model.